Arching in concrete slabs strengthened with near surface mounted fibre reinforced polymers. (1st April 2019) - Martin, Tony; Taylor, Su; Robinson, Desmond; Cleland, David
Abstract: This paper outlines basalt fibre reinforced polymer (BFRP) and carbon fibre reinforced polymer (CFRP) strengthening of laterally restrained concrete floor slabs. In-plane restraint has previously been shown to enhance slab capacity due to the development of internal compressive membrane action (CMA), which is not generally included in codified strength assessments. By installing fibre reinforced polymers (FRPs) using the near surface mounted (NSM) technique, disturbance to the existing structure can be minimised. The span-to-depth ratios of test slabs were 20 and 15 and these were constructed with normal strength concrete (∼40 N/mm 2 ) with 0.15% steel reinforcement. 0.10% FRP (either BFRP or CFRP), was used to strengthen samples which were then compared with control samples. Investigations showed that FRP strengthening and CMA are generally separate, with limited overlap in terms of their contribution to capacity increase. Recommendations are then made for designers to better determine the capacity of FRP strengthened restrained slabs.